To All Who Should Be Concerned - Robinson, Dylan (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2019)
xexé:yltholetsel te sqwà:ls te'íle tl'ekwelep tél:exwatlha ye s'í:wes shxwélméxwelh. xéyxewetholetsel. ólew híth kw'elsu ó:lmethome. eyeléwthelh. tl'élexw kw'a's qel í:weselep. éy kw's totí:ltset, lheqtó:léstexwtset te syó:ys te í. ewe qelélweselep. xwelítem skwukwelstéleq talhwélep, maytólxwchapcha (xwélmexw, lets'ô:lmexw) tlowáyél, qas te wáy:eles.This letter describes some of the foundation and basic structural changes that must be implemented by music programs in order to move toward decolonial forms of music education. The letter serves as one starting point for such change among many that must always be led by Indigenous, Black, Latinx, Asian and other scholars / artists of colour (IBPOC) who live and work in the locations where music programs are based. Community-led change is imperative in order to avoid the replication of normative systems of music education that merely include diverse content. The letter asserts that while curricular change and hiring of IBPOC scholars constitute one part of this change, it might also be understood as a form of additive inclusion. Models of additive inclusion proceed by placing diverse content within normative, white supremacist structures of pedagogy that remain unchanged. Additive inclusion consequently maintains the power of those who choose what content to include, rather than giving over space for IBPOC leadership to determine the parameters for change, and to determine how foundational structures of music education should be dismantled and renewed.